1998
DOI: 10.1159/000030007
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between DNA Content, Expression of Ki-67 Antigen of Tumor Cells and Immunophenotype of Lymphocytes from Malignant Pleural Effusions

Abstract: Malignant cells isolated from 26 malignant pleural effusions, collected from patients bearing metastatic carcinoma, were examined using flow cytometry. Expression of Ki-67 antigen, DNA ploidy, S phase fraction, DNA index of tumor cells and the percentage of aneuploid cell populations were determined. Lymphoid cells from the same malignant effusions and from 10 nonmalignant ones were examined using a panel of monoclonal antibodies (mAb) versus several CD antigens. While the percentages of T cells (CD3+, CD4+, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
0
17
1
Order By: Relevance
“…The Houston VA study population consisted of only men (3). Two other noteworthy studies in the literature examined only pleural effusions caused predominantly (6) or solely (8) by lung cancer. The study by Guzman et al (7) involved only ovarian cancer‐related ascites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Houston VA study population consisted of only men (3). Two other noteworthy studies in the literature examined only pleural effusions caused predominantly (6) or solely (8) by lung cancer. The study by Guzman et al (7) involved only ovarian cancer‐related ascites.…”
Section: Discussionmentioning
confidence: 99%
“…In numerous reports, the degree of tumor infiltration by NK cells correlates directly with prognosis (1, 2). Comparison of percentage of NK cells in malignant versus benign cavity effusions has yielded conflicting results, with some studies showing a significant increase (3–5), others a significant decrease (6), and still others showing no difference (7, 8). One frequently quoted 1996 study from the Houston Veterans Affairs (VA) Hospital reported a highly statistically significant ( P < 0.00001) association between a high percentage of NK cells and metastatic malignancy in pleural and peritoneal effusions and asserted that (flow cytometric) measurement of NK cells in effusions was “a new, sensitive means of detecting carcinoma” (3).…”
mentioning
confidence: 99%
“…In effusion cytology, FCM has previously been used mainly to detect DNA-aneuploid cells populations, [15][16][17][18][19][20] sometimes in combination with immunophenotyping of admixed lymphoid cells. 21,22 Because of the high reproducibility of FCM and its inherent ability to study multiple markers simultaneously, we have recently begun to evaluate its potential role in the diagnosis and characterization of effusion specimens. 12,23,24 Ber-EP4 was found on 94% of carcinomas in the present study, in agreement with our earlier reports.…”
Section: Discussionmentioning
confidence: 99%
“…To date, flow cytometry has mainly been used to detect aneuploid cell populations, [3][4][5][6][7][8] sometimes in combination with immunophenotyping of admixed lymphoid cells. [9][10][11] The number of natural killer (NK) cells has been used to predict the presence of malignant cells in serous eVusions. 12 However, limited data are available regarding flow cytometric immunophenotyping of epithelial cells in eVusions.…”
mentioning
confidence: 99%